Kerusakan Lingkungan Akibat Pertambangan Nikel di Kabupaten Kolaka Melalui Pendekatan Politik Lingkungan - Agussalim, Muhammad Sibgatullah; Ariana, Ariana; Saleh, Ramlah (LP2M IAIN Palopo, 2023)
AbstractThe impact of environmental damage caused by mining activities, especially nickel mining, is still a common problem. There is no shared awareness to protect the environment so that it remains balanced from various parties, namely companies that carry out mining production, the government as a regulatory policy, and the community as the party that operates environmental damage due to mining production activities. This study uses an environmental and political approach to describe the problems of environmental damage. The method used in this research is qualitative research. Data and information sources were obtained from observations, discussions, and references to literature documents from books, journals, and electronic information media. The results of this study found environmental damage due to nickel mining due to several things, namely mining production activities in forest areas, problem permissions of mining and the dynamics between profit interests and environmental damage resulting from mining activities. Keywords: Environmental Damage, Environmental Politics, Government, Nickel mining.Â